Hubungan Penagihan Dadah Dengan Perlakuan Jenayah : Pengaruh Faktor-Faktor Psikososial Dan Institusi Terpilih - Yahya, Don (1999)
This study attempts to investigate the relationship that influence psychosocial and selected institutional factors such as self-esteem, family members, peers, society and learning institutions leading to criminal behaviour among drugs addicts. The study also shows the relationship between selected addiction factors with institution and psychosocial variable. A research model has been formulated by researcher from Chein (1984) psychosocial and epidemiological factor teory to investigate the relationship. This research was conducted in Karangan, Kedah and Kampung Selamat, Seberang Prai, Pulau Pinang, Drugs Rehabilitation Centre which involving 300 trainee. Each trainee is given a set of questionnaires which consist of six sections. The sections are self information and criminal behaviour, Coopersmith Self-Esteem Inventory (CSEI) (11967) family members influence questionnaires (Beschner & Friedman, 1979) peers influence questionnaires, society influence questionnaires and learning institution influence questionnaires has been distributed. The data obtained will be analysed by using Pearson Correlation (r), t-test and Regression analysis, Result shows that self-esteem aspects has no significant relationship with crime behaviour. Factors such as age duration of addiction and number of times being sent to rehabilitation centres has no relationship with the self-esteem of the respondent. Nevertheless, there is a significant difference between self-esteem scores among drug addicts who stay in their urban as opposed to the rural areas. The study also shows that family members influence has no significant relationship with criminal behaviour; the age of the addicts has no significant relationship with family members influence. This study also reveals that the duration of addiction and number of times being sent to rehabilitation centre has significant relationship with family members influence, but family members influence has no significant differentiation based from place of stay. The study also shows that there is no significant relationship between peers influence and criminal behaviour with addiction factors. It also reveals that society influence has significant relationship with criminal behaviour. The duration of addiction and number of times being sent to rehabilitation centre has significant relationship with society influence. Finally, the study shows that learning institution influence has no negative significant relationship with criminal behaviour, where as the duration of addiction and number of times being sent to Rehabilitation Centre has significant relationship with learning institution influence. Furthermore this study found that the age of drug addicts and the location of drug addicts place of stay has no relationship significant differentiation with learning institution influence. Regression test shows that the number of times being sent to Rehabilitation Centre and society influence are dominant variables which influence crime behaviour by drug addicts followed by family members influence and learning institution influence. Generally, on the whole, self-esteem and peers have no relationship between criminal behaviour. So, this research model cannot be fully supported.